2021
DOI: 10.1039/d0cc08359c
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic hydrogen production of porphyrin nanostructures: spheres vs. fibrils, a case study

Abstract: Herein, we illustrate the preparation of a covalent connected peptide-porphyrin hybrid (Fmoc-FF-(Zn)Por). Thorough investigation of its self-organization features demonstrated that Fmoc-FF-(Zn)Por can self-assembly into spheres and fibrils by using different...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…In this concept, we synthesized FmocFF-ZnTPP and examined its well-defined nanostructures as photocatalysts in H 2 production. 87 In detail, following the ''good'' and ''poor'' solvent method we obtained spherical and fibrillar self-assembling architectures from the same porphyrin molecule, which presented much different catalytic activity towards H 2 evolution. After photo-deposition of Pt NPs on the fibrillar nanostructures in the presence of AA as SED, H 2 generation was achieved with a rate of 1.96 mmol g À1 h À1 (Table 3, entry 23).…”
Section: Review Articlementioning
confidence: 99%
“…In this concept, we synthesized FmocFF-ZnTPP and examined its well-defined nanostructures as photocatalysts in H 2 production. 87 In detail, following the ''good'' and ''poor'' solvent method we obtained spherical and fibrillar self-assembling architectures from the same porphyrin molecule, which presented much different catalytic activity towards H 2 evolution. After photo-deposition of Pt NPs on the fibrillar nanostructures in the presence of AA as SED, H 2 generation was achieved with a rate of 1.96 mmol g À1 h À1 (Table 3, entry 23).…”
Section: Review Articlementioning
confidence: 99%
“…To examine the effect of dye/catalyst ratio on the performance of the photocatalysts, different concentrations of the MG dye aqueous solution (5,10,15,20,30, and 40 mg L −1 ) with a fixed amount of catalyst (5 mg each time) were used for each time. From Figure S13, it was revealed that the degradation rate gradually decreased as the concentration of MG dye increased.…”
Section: Photocatalytic Performance For the Degradation Of Mg Dyementioning
confidence: 99%
“…These nanomaterials display unique features, including large surface areas and high physicochemical stability, compared to their parent compounds. Highly ordered and versatile geometric features render these materials suitable for applications in other fields, including chemical sensing [18], molecular recognition [19], catalysis [20], solar energy conversion and storage [21], and biomedical purposes [22]. Porphyrin molecules aggregate in solution and self-assemble to form larger stable molecules.…”
Section: Introductionmentioning
confidence: 99%
“…The strong bonding of aryloxides to Sn(IV) porphyrins was the main driving force for the formation of these porphyrin arrays. 45 All six triads were fully characterized by various spectroscopic techniques, including elemental analysis, ESI-mass spectrometry, 1 H NMR, UV-vis, and fluorescence spectroscopy, and field emission scanning electron microscopy (FE-SEM).…”
Section: Syntheses and Characterization Of Triadsmentioning
confidence: 99%